2018
DOI: 10.5430/afr.v7n2p39
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tax Amnesty Announcement towards Share Performance and Market Reaction in Indonesia

Abstract: The Indonesian Government reviewed back the tax amnesty in 2016. Various reactions came up along with the announcement of tax amnesty, the investors did not accept-which led to the announcement of the Tax Forgiveness regulation through the market reactions and stock market performances in Indonesia Stock Exchange. This research is to analyze event study using information based on government-related announcements to show the impact of the new regulation towards stock performance and market reaction. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
3
0
3
Order By: Relevance
“…Hence, their performance will not reduce substantially. According to Agustina et al (2018), job stress will affect individual work performance. High stress conditions will have an impact on low performance, high stress will have an impact on not achieving work, and will become an obstacle to others, thereby resulting in low performance.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, their performance will not reduce substantially. According to Agustina et al (2018), job stress will affect individual work performance. High stress conditions will have an impact on low performance, high stress will have an impact on not achieving work, and will become an obstacle to others, thereby resulting in low performance.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the DE is sensitive to taxes and the decisions of traders are affected by the rate of taxes [40]. In this context [41], observed the impact of security transaction taxes and inferred that it has an adverse impact on stock market participants and reduces profitability. Studies by [42] reveal that to reduce tax liabilities, traders wind up their winning positions as the year approaches.…”
Section: Cost-consciousnessmentioning
confidence: 99%
“…Pernyataan ini melatarbelakangi peneliti untuk menguji apakah dengan adanya insentif pajak ini dapat memoderasi pengaruh book-tax differences terhadap trading volume activity. Penelitian terdahulu terkait efek insentif perpajakan terhadap reaksi pasar menunjukkan bahwa terdapat perbedaan rata-rata return saham, rata-rata abnormal return saham, dan volume perdagangan saham sebelum d an sesud ah pengampunan pajak (Agustina et al, 2018a). Selain itu investor memiliki r espon asimetris terhadap perubahan tarif pajak yaitu investor lebih menanggapi penurunan tarif pajak daripada kenaikan tarif pajak untuk saham (Agapova & Volkov, 2021).…”
Section: Pendahuluanunclassified
“…Hal ini berarti bahwa dengan adanya insentif pajak yakni tambahan penurunan tarif pajak sebesar 5% pada tahun 2019 dan 3% pada tahun 2020 ditangkap sebagai sinyal baik oleh invest or sesuai dengan teori sinyal. Hasil ini konsisten dengan hasil penelitian ter dahulu dari (Agapova & Volkov, 2021) dan (Agustina et al, 2018b). Per ubahan volume perdagangan saham di bursa menjadi indikator penting bagi investor dalam pengambilan keputusan transaksi di pasar saham.…”
Section: Gambar 1 Model Penelitianunclassified
See 1 more Smart Citation